E.QUALITY@BT - Macmillan, Roderick H. (Internet research, 1996)
Explains that an on-line ISO 9001-based management system has been developed using the World Wide Web (WWW), a hypermedia system and part of the Internet. Subject matter is presented as an alphabetical list of linked encyclopedia-style entries. Numerous navigational techniques are available, and the system allows the user several different routes to particular information. ISO 9001 and Tickit cross-references are incorporated, together with linked process diagrams, a topic-based change log and electronic forms. The level of detail presented on screen may be controlled by users.